FERMENTASI KECAP DARI BEBERAPA JENIS KACANG-KACANGAN DENGAN MENGGUNAKAN RAGI MUTAN Aspergillus sp. K-1 DAN Aspergillus sp. K-1A - Elidar Naiola; Yati Soedaryati Soeka (BERITA BIOLOGI, 2007)
This study was focused on the selection of type of beans for kecap production. The mold fermentation or kecap koji making process was conducted in small scale at room temperature for 3 days and the brine fermentation for 2 weeks at room temperature.Product were analyzed for biochemical (total nitrogen, formol nitrogen, and total water soluble nitrogen) content. It was found that the final composision of kecap mash were mainly due to brain fermentation and by activities of strains showed varies effect to total nitrogen (TN), formol nitrogen (FN), and total water soluble nitrogen (WN).Kecap mash produced using kedelai, hiris and tolo inoculated with Aspergillus sp. K-1 containing formol nitrogen 0.58%, 0.65% and 0.57%, respectively.Meanwhile using Aspergillus sp. K-1A producing kecap mash with formol nitrogen were 0.75%, 0.75%, 0.65%, respectly. The ratio of WN to TN of the kecap mash from hiris and tolo were up to 50%, while the ratio of FN to TN varies, which was influenced by the koji used.Based on the chemical properties above, it can be recommended that hiris can be used for kecap production though requires extensive researches.